Redefine oral health: a call for inclusivity in the concept of oral health - Foláyan, Moréniké Oluwátóyìn; Ndembi, Nicaise; Abodunrin, Olunike Rebecca; Haire, Bridget (Frontiers in Oral Health, 2025)
Current, globally accepted definitions of oral health emphasize pain-free functionality, expressive capacity, and specific psychosocial dimensions that contribute to self-confidence, well-being, and societal participation. However, these definitions inadvertently exclude diverse lived experiences by framing oral health solely through a lens of “normal” functionality and absence of discomfort, failing to consider the ways in which oral health can be experienced uniquely by different individuals and communities. The narrow focus on “pain-free” oral health excludes valid aspects of sexual expression, which may involve consensual oral activities that some find pleasurable even if associated with discomfort. This manuscript examines the limitations of the WHO and FDI definitions of oral health, critiques their exclusion of minority perspectives, and advocates for a more inclusive, holistic approach. Such an approach recognizes the complex and varied ways oral health intersects with identity, intimacy, and societal norms. Normalizing discussions on oral sexual health are essential to advancing a comprehensive understanding of well-being and reducing stigma around sexual minority experiences. Expanding oral health definitions to accommodate broader conceptions of intimacy and pleasure can enhance public health policy, clinical practice, and education, fostering a comprehensive understanding of well-being that reduces stigma around sexual minority experiences and further marginalization of sexual minorities in accessing inclusive care.